Review of Cloud Storage Techniques - K, Madhura; Mangai, Alamelu J (International Journal of Computer Sciences and Engineering, 2025)
The term “cloud” is very common term and is used in both biological plus technical fields. During rainy reasons cloud plays a very important role in the life of human beings as it stores all molecules for showering the water and humans can preserve the water for future living. In the same way, in technical fields it offers a list of facilities for the user with respect to data such as data storage, security to data, data sharing, and data preservation for the future, updation and maintenance. Cloud is one such platform which allows the user to store the data and application together at one place and it is made available irrespective of the place of access at any time. Cloud can be used by an individual or a company for many purposes such as storing, retrieving and sharing documents, photos, e-mails, etc. The big question which always runs on every researcher’s mind is the need of cloud. The main problem is to find a place to store the huge growing amount of data. According to a survey done by Peter Lyman and HAL R Varian, world produces approximately two Exabyte’s of data every year which means that each individual contribution is around 250 megabytes. So it is possible to fit this much amount of data in any storage medium like papers, magnetic tapes, disks and drives. This paper gives a brief insight into the existing cloud storage techniques which are used by organizations.